Plant variety protection-newly registered PhilRice inbred rice genotypes for irrigated lowland (The Philippine Journal of Crop Science, 2013)
Five PhilRice-bred rice genotypes were approved by the Bureau of Plant Industry-Plant Variety Protection Office in December 2012. These genotypes were selected after it underwent (distinct, uniform, stable) test in 2012 at the Philippine Rice Research Institute Central Experiment Station. PR32220 was delivered from IR69800-5-3-1-1/LRJ-5-5 cross. It matures in 117 days, 106cm in height and with an average of 11 tillers per plant. The yield was 8.2 t ha-1 in DS and 4.8 t ha-1 in WS. PR35766 was delivered from PSB Rc96/ AR32-19-3-3 cross. It is semi-dwarf at 105 cm, with medium-tillering of 14 tillers per plant, and matures in 110 days. In 2012, the yield was 6.4 t ha -1 during DS and 5.0 t ha -1 in the WS. It has a premium total milled rice yield of 71.9% which is comparable to the check PSB Rc18. PR37598 was delivered from C754WH-12-2-1/JASMINE cross. It matures in 112 days, has intermediate plant height of 113 cm, with medium tellering of 12 tillers per plant. The yield was 7.7 ha -1 in the DS and 4.1 t ha -1 in WS. It has low amylose content of 18.0% making it generally soft and sticky when cooked. PR39728 was delivered from MX-B-27/NSIC Rc144 WT cross. It matures in108 days, has intermediate height at 120 cm and with medium-tillering of 10 tillers per plant. The yield was 9.0 t ha -1 during DS and 4.4 t ha -1 in WS. it has a very good brown rice yield which is significantly superior to the 2 check varieties with premium grade classification of 79.5%